Feeding Response of Coptotermes curvignathus and Coptotermes gestroi (Isoptera: Rhinotermitidae) to Different Wood of Hevea Species - Sajap, Ahmad Said; Sahri, Mohd Hamami; Mohd Kasim, Mohd Roslan (2009)
Rubber wood, Hevea brasiliensis, is one the most important resources for the timber industry in Malaysia. In an effort to increase the supply of quality rubber wood to the timber industry in Malaysia, several Hevea species, H. pauciflora, H. spruceana, H. guainensis and H. nitida, from Brazil were introduced into Malaysia and tested for their growth performances and wood properties. In this study, wood blocks from these Hevea species were exposed to subterranean termites, Coptoptermes curvignathus and Coptotermes gestroi in laboratory and field trials. The results show that no significant differences in the daily feeding rates that were detected when the wood blocks were forcefully given to the termites. However, a significant variation in the feeding rates of both termite species was observed in choice and field trials. The results from these trials show that H. pauciflora was the most preferred and Hevea spruceana was the least preferred wood.